Supernew Supergraphics - Brook, Tony; Shaughnessy, Adrian; Schrauwen, Sarah (London : Unit Editions, 2014)
Supernew Supergraphics is a collection of the best architectural, environmental and interior graphic design. This all-new book shows how the current generation of designers and architects are blasting typography and graphic forms across walls - even landscapes. It shows how they are distorting space and warping entire buildings with colour, typographic messages and abstract shapes.
boek